Quantum Dots Based Electrochemiluminescent Immunosensor for Ultrasensitive and Specific Determination of Mercury (II) Ions Using Gold Nanoparticles and a Monoclonal Antibody. Issue 1 (1st January 2015) - Zhang, Jing; Shi, Pengwei; Yan, Panpan; Wang, Mingbo; Tang, Qinghui; FudongCai,; Deng, Anping; Li, Jianguo
Abstract : In the present work, a rapid and ultrasensitive electrochemiluminescent (ECL) competitive immunoassay for mercury (II) based on CdSe quantum dots (QDs), gold nanoparticles (GNPs) and specific monoclonal antibody (mAb) against Hg 2+ has been developed. GNPs were creatively applied as substrate and electron transfer accelerator, which would load a large number of coating antigen and amplify the electrochemical signal. Taking advantage of the specific mAb against Hg 2+, a cost-effective and selective GNPs/Ovalbumin-MNA-CH3 Hg/mAb-QDs immunosensor was fabricated. A competitive immunoassay format was selected as a way of quantifying Hg 2+, where Hg 2+ in a sample would compete with the corresponding coating antigen for the limited QDs labeled mAb. With the coreactant S2 O8 2−, a strong ECL signal was observed and the decrease of the ECL intensity is linear to the logarithm of the mercury (II) concentration within the range of 0.01 to 50 ng mL −1, with a detection limit of 2.6 pg mL −1, much lower than previous methods. To our knowledge, this ECL immunoassay applied GNPs as substrate combined with specific monoclonal antibody detecting Hg 2+ is presented for the first time. The application in real samples with favorable results and the highly sensitivity and selectivity further indicate that this ECL immunosensor is feasible for Hg 2+ detection and enlarge the application of GNPs and monoclonal antibody in monitoring heavy metals.